Expectativas de inflação sob o regime de metas no Brasil - Silva, Fábio José Ferreira da (2006)
This thesis evaluates the inflation forecasts surveyed by the Brazilian Central Bank (Banco Central do Brasil, BC) and used in its monetary policy decisions. Proceeding as in Thomas Jr. (1999), we found that market surveys of inflation expectations, published in the Boletim Focus, are biased and inconsistent, and hence unable to foresee future changes in inflation. Estrella e Mishkin (1997), Kozicki (1997) e Kotlan (1999) used models based on the yield spread to predict inflation. We adapted these models for the Brazilian case and we obtained significant results for the short and medium run, showing that the yield spread can subsidize BC’s monetary policy decisions. However, because Brazil has a short term yield curve, this property was not detected beyond 9 months. With economic stabilization, we expect this curve to lengthen, allowing this instrument to become more powerful.